A nationwide study on Borrelia burgdorferi s.l. infection rates in questing Ixodes ricinus: a six‐year snapshot study in protected recreational areas in England and Wales. Issue 3 (7th January 2021) - Cull, B.; Hansford, K. M.; McGinley, L.; Gillingham, E. L.; Vaux, A. G. C.; Smith, R.; Medlock, J. M.
Abstract: Understanding the variation in Borrelia burgdorferi s.l. infection rates in Ixodes ricinus ticks is important for assessing the potential for Lyme borreliosis transmission. This study aimed to investigate infection rates of B. burgdorferi s.l. bacteria in I. ricinus across 24 field sites in England and Wales, focussing on protected recreational areas in National Parks (NPs) and Areas of Outstanding Natural Beauty (AONBs), to provide comparable data across multiple years to assess spatio‐temporal changes in B. burgdorferi s.l. infection. Working with park rangers, questing ticks were collected each spring from 2014 to 2019. A subset of ticks, 4104 nymphs, were analysed using a pan‐ Borrelia qPCR assay, as well as a Borrelia miyamotoi ‐specific qPCR, and sequenced to determine Borrelia burgdorferi s.l. genospecies. Site‐specific B. burgdorferi s.l. infection rates in I. ricinus nymphs varied from 0% to 24%, with overall infection rates ranging from 2.5% to 5.1% across the years. Genospecies composition of sequenced samples was 62.5% B. garinii, 20.3% B. valaisiana and 17.2% B. afzelii. Borrelia miyamotoi was detected in 0.2% of ticks. This study increases our knowledge on B. burgdorferi s.l.. infection in areas used by the public for outdoor activity across England and Wales, highlighting the spatial and temporal variability which can impact the changing risk to humans from infected tick bites. Abstract : Long‐term 6 year survey of Borrelia burgdorferi s.l. infected Ixodes ricinus ticks in England and Wales found mean infection rates of 3.9%. The high infection rates were reported in southern England with means >10% with lowest infection rates in Wales. The most common B. burgdorferi s.l. genospecies was B. garinii (∼50%). Borrelia miyamotoi was found at very low infection rate (0.2%).